Heterologous expression and characterization of a new lipase from Pseudomonas fluorescens Pf0–1 and used for biodiesel production. Issue 1 (December 2017) - Liu, Wu; Li, Menggang; Yan, Yunjun
Abstract As a kind of important biocatalysts, Pseudomonas lipases are commonly applied in various industrial fields.Pflip1, a new extracellular lipase gene fromPseudomonas .fluorescens Pf0–1, was first cloned and respectively expressed inEscherichia coli BL21(DE3) andPichia pastoris KM71, the recombinant proteins Pflip1a and Pflip1b were later purified separately. Then Pflip1a was further characterized. The optimum pH of Pflip1a was 8.0 and its optimal temperature was 70 °C. After incubation at 70 °C for 12 h, Pflip1a could retain over 95% of its original activity. It showed the highest activity towardsp -nitrophenyl caprylate. Moreover, its activity was profoundly affected by metal ion, ionic surfactants and organic solvents. Furthermore, the two obtained recombinant lipases were immobilized on the magnetic nanoparticles for biodiesel preparation. The GC analysis showed that for the immobilized lipases Pflip1b and Pflip1a, the biodiesel yield within 24 h respectively attained 68.5% and 80.5% at 70 °C. The activities of the two immobilized lipases still remained 70% and 82% after 10 cycles of operations in non-solvent system. These characteristics and transesterification capacity of the recombinant protein indicated its great potential for organic synthesis, especially for biodiesel production.